Exposure to Helicobacter pylori infection in early childhood and the risk of allergic disease and atopic sensitization: a longitudinal birth cohort study - Amberbir, Alemayehu; Medhin, G; Abegaz, W.E.; Hanlon, C.; Robinson, K.; Fogarty, Andrew W.; Britton, John; Venn, A.; Davey, G. (Wiley, 2014)
Background: An inverse relation between Helicobacter pylori infection and allergic disease has been reported by a range of independent epidemiological studies, but evidence from longitudinal studies is scarce.